Mixing ventilation driven by two oppositely located supply jets with a time-periodic supply velocity: A numerical analysis using computational fluid dynamics. Issue 4 (April 2020) - van Hooff, T.; Blocken, B.
Ventilation is of primary importance for the creation of healthy and comfortable indoor environments and it has a significant impact on the building energy heating and cooling demand. The aim of this study is to assess the application of time-periodic supply velocities to enhance mixing in mixing ventilation cases to reduce heating and cooling energy demands. This paper presents computational fluid dynamics (CFD) simulations of a generic mixing ventilation case, in which the time-averaged velocities and pollutant concentrations from a reference case with constant supply velocities were compared with those obtained from a case with time-periodic supply velocities (sine function). The unsteady Reynolds-averaged Navier-Stokes (URANS) CFD simulations indicate that the use of time-periodic supply velocities can reduce high pollutant concentrations in stagnant regions, reduces the overall time-averaged pollutant concentrations and increases contaminant removal effectiveness with about 20%. The influence of the period of the sine function was assessed and the results showed that for the periods tested, the differences are negligible. Finally, the URANS approach was compared with the large eddy simulations (LES) approach, indicating that URANS leads to very similar results (NMSE < 3.2%) as LES and can thus be regarded as a suitable approach for this study.